Mengelola Kesepian: Self-Compassion dan Dukungan Sosial dalam Kehidupan Mahasiswa Rantau - Emilia Nur Aini Putri; IGAA Noviekayati; Aliffia Ananta (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract Overseas students in their late teens are prone to loneliness because they have to adapt to a new environment without direct support from their families. This study aims to determine the role of self-compassion and social support in reducing loneliness levels among overseas students. This study uses a correlational quantitative approach with 183 overseas students aged 18–21 years as participants selected using incidental sampling techniques. The instruments used include scales measuring loneliness, self-compassion, and social support. Data analysis was conducted using correlation and regression tests. The results indicate that both self-compassion and social support are significantly negatively correlated with loneliness. This means that the higher the levels of self-compassion and social support, the lower the levels of loneliness experienced by students. These findings highlight the importance of psychological interventions that foster self-compassion and build strong social networks. Keywords: Social Support, Lonelines, Students Away from Home Late Adolescents, Self-Compassion. Abstrak Mahasiswa rantau pada tahap remaja akhir rentan mengalami kesepian karena harus beradaptasi dengan lingkungan baru tanpa dukungan langsung dari keluarga. Penelitian ini bertujuan untuk mengetahui peran self-compassion dan dukungan sosial dalam mengurangi tingkat loneliness pada mahasiswa rantau. Penelitian ini menggunakan pendekatan kuantitatif korelasional dengan 183 mahasiswa rantau berusia 18–21 tahun sebagai partisipan yang dipilih menggunakan teknik insidental sampling. Instrumen yang digunakan meliputi skala loneliness, self-compassion, dan dukungan sosial. Analisis data dilakukan menggunakan uji korelasi dan regresi. Hasil menunjukkan bahwa baik self-compassion maupun dukungan sosial berhubungan negatif signifikan dengan loneliness. Artinya, semakin tinggi tingkat self-compassion dan dukungan sosial, semakin rendah tingkat kesepian yang dirasakan mahasiswa. Temuan ini menunjukkan pentingnya intervensi psikologis yang menumbuhkan welas asih pada diri dan membangun jejaring sosial yang kuat. Kata kunci: Dukungan Sosial, Loneliness, Mahasiswa Rantau, Remaja Akhir, Self-Compassion.